Synthesis of SnO₂ Nanoparticles from Metals by Electrochemical Approach: An Innovative Solution for Functional Materials - Rahmi Rahmi; Tom Downs; Malësore Pllana-Zeqiri (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study was to produce SnO2 nanoparticles by electrochemical method using tin metal and hydrochloric acid as electrolyte solution. Methodology: Synthesis of SnO₂ nanoparticles was carried out using an electrochemical method with tin electrodes and HCl solution. Variations in potential (10–100 V) and HCl concentration (0.005–0.06 M) were observed for optimization. Characterization using UV-Vis, FTIR, XRD, and Zeta Sizer showed that this method was effective in producing SnO₂ nanoparticles with crystal structure, composition, and size distribution that could be optimized. Main Findings: This study successfully synthesized SnO₂ nanoparticles from tin metal using an electrochemical method with HCl solution. The optimum potential for electrolysis was 60 V, with a HCl concentration of 0.06 M producing the largest nanoparticles (83.11 nm) at a wavelength of 207 nm and an absorbance of 3.068. XRD characterization showed a diffraction pattern according to the SnO₂ standard, while FTIR confirmed the Sn–O vibration at 580 cm⁻¹. Novelty/Originality of this study: The characterization results show a correlation between HCl concentration with nanoparticle size and absorbance wavelength, which provides new insights into controlling the optical properties and structure of SnO₂ nanoparticles.